Front de lutte du Kampuchea Krom : (s.n.])
Covertitle also in Khmer. - Photobook on the Liberation Front of Kampuchea Krom (Front de Liberation du Kampuchea Krom, FLKK), representing the Khmer Krom of the Mekong Delta, led by Chau Dara.